Inherited salt-losing tubulopathies are associated with immunodeficiency due to impaired IL-17 responses - Rhys D. R. Evans (Nature Portfolio, 2020)
Salt levels in culture affect the polarisation of Th17 cells, which normally protect the host from fungal and bacterial infections. Here, the authors study patients with salt-losing tubulopathies (SLT) to find that, while Th17 immunity is dampened in SLT patients, their Th17-inducing signaling pathways are intact and can be reinvigorated by exogenous salt.